IMPROVEMENT OF THE GAS TEMPERATURE CONTROL SYSTEM IN FRONT OF THE HIGH-PRESSURE TURBINE OF THE GTK-10 GAS PUMPING UNIT - Зварич, Галина; Матеїк, Галина (SWorldJournal, 2024)
The paper considers an improved gas temperature control system in front of the high-pressure turbine of a gas pumping unit of the GTK-10 type. The relevance of the topic is due to the need to increase the efficiency and reliability of gas pumping units, e